Analisis Evaluasi Program Pendidikan Dalam Pembelajaran Di Sekolah Dasar Menggunakan CIPP : Sebuah Systematic Literature Review - Asriningrum, Novita; Maulina, Eva; Muhibbin, Ahmad; Susilo, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Narrative Literature Review (NLR) approach was employed in this study to examine various scientific articles concerning the evaluation of educational programs in elementary schools based on the Context, Input, Process, Product (CIPP) model. The data analysis involved stages of identification, selection, categorization, and synthesis of diverse research findings according to the four core components of the model. The literature review demonstrated that the success of a program largely depends on its relevance to the needs of students and schools. Other determining factors include teachers’ competencies, the availability of facilities, managerial support, as well as the effectiveness of program implementation and supervision. From the product component perspective, most programs were found to generate positive impacts on improving student learning outcomes, teaching quality, teacher competence, and institutional quality. However, implementation in practice continues to face challenges, including budget constraints, limited resources, and insufficient training opportunities. Overall, the CIPP model serves as a comprehensive and effective evaluation instrument for assessing the achievement of educational programs. This approach also provides a strong foundation for decision-making and the sustainable development of learning practices in elementary schools.